2018
DOI: 10.1002/ehf2.12385
|View full text |Cite
|
Sign up to set email alerts
|

Updates in heart failure: what last year brought to us

Abstract: EpidemiologyHeart failure (HF) is common, and HF with preserved ejection fraction (HFpEF) has become its most frequent clinical presentation because of ageing of the population and decreasing prevalence of coronary artery disease (CAD). 1,2 An analysis of all studies using echocardiography to estimate the prevalence of cardiac dysfunction in subjects aged ≥60 years showed a median prevalence of 36.0% (range 15.8-52.8%) and 5.5% (range 3.3-9.2%) for 'isolated' left ventricular (LV) diastolic dysfunction and LV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 217 publications
(230 reference statements)
0
10
0
1
Order By: Relevance
“…Another explanation is that the mortality estimated in this meta-analysis was all-cause mortality, because it included studies that had enrolled patients with various comorbidities (e.g., atrial fibrillation, chronic obstructive pulmonary disease, chronic kidney disease, diabetes) and heart failure may have been just one of the multiple conditions that contributed to mortality. Previous studies have identified that heart failure patients with comorbidities have a poor survival rate [40,41]. In this context, support for managing comorbidities is essential in interventions for improving heart failure patients' self-care abilities.…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation is that the mortality estimated in this meta-analysis was all-cause mortality, because it included studies that had enrolled patients with various comorbidities (e.g., atrial fibrillation, chronic obstructive pulmonary disease, chronic kidney disease, diabetes) and heart failure may have been just one of the multiple conditions that contributed to mortality. Previous studies have identified that heart failure patients with comorbidities have a poor survival rate [40,41]. In this context, support for managing comorbidities is essential in interventions for improving heart failure patients' self-care abilities.…”
Section: Discussionmentioning
confidence: 99%
“…HF treatment has progressed considerably in recent years, leading to a noticeable improvement in prognosis. This is true of pharmacological treatments such as combinations of angiotensin II receptor blockers and neprilysin inhibitors (valsartan/sacubitril) and gliflozins like empagliflozin and dapagliflozin [ 4 , 5 ]. Also effective are some non-pharmacological treatments, particularly the patient taking ownership of the disease, following dietary and lifestyle guidelines, and tackling sedentary behavior through a patient education program and the establishment of a clinical pathway for the follow-up of patients with CHF [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Current guidelines also differentiate LVEF in the range of 40-49% (HF with mid-range ejection fraction). 4,5 To date, HF with preserved ejection fraction is the most common manifestation of HF with a median prevalence of 4-7% as compared with 2-6% for HFrEF in patients aged 60 years and older, using echocardiography. 6 Left ventricular diastolic dysfunction without manifest HF is even more frequent in these patients with a median prevalence of 16-53% in comparison with 3-9% for systolic dysfunction.…”
Section: Introductionmentioning
confidence: 99%